New Student Orientation White Paper - Jessica Lavariega Monforti::::::; Ernesto Guerrero::::::; Veronica Guerrero::::::; Monica Rivas::::::; Ariana Robles::::::; Catherine Villa-Real::::::
The academic literature shows that creating an integrated first year experience program that fosters a successful undergraduate student experience through strategic programming that focuses on positive academic transitions and the development of learning communities can move the needle significantly. The authors present an argument in favor of developing a more integrated and intentional new student onboarding experience, from recruitment and admission through enrollment, for first-time, full time and transfer students that is both culturally relevant and academically grounding.